2015
DOI: 10.1631/jzus.b1400204
|View full text |Cite
|
Sign up to set email alerts
|

Ginsenoside Rg1 ameliorates oxidative stress and myocardial apoptosis in streptozotocin-induced diabetic rats

Abstract: Abstract:We evaluated the cardioprotective effects of ginsenoside Rg1 in a diabetic rat model induced with high-fat diet and intraperitoneal injection of streptozotocin. Ginsenoside Rg1 was injected intraperitoneally for 12 weeks. Myocardial injury indices and oxidative stress markers were determined. Changes in cardiac ultrastructure were evaluated with transmission electron microscopy. Myocardial apoptosis was assessed via terminal deoxynucleotidyl transferase (TDT)-mediated DNA nick-end labeling (TUNEL) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
56
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(60 citation statements)
references
References 46 publications
4
56
0
Order By: Relevance
“…Researchers have found PI3K/Akt to be a powerful survival pathway in numerous systems; cells can accelerate apoptosis by inhibiting PI3K and decelerate apoptosis by activating Akt (Hemmings and Restuccia, 2012). It was found that a decrease of caspase-9 activation could indicate the cardioprotective effects against diabetic cardiomyopathy by inhibiting cardiomyocyte apoptosis (Sun et al, 2014;Yu H.T. et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Researchers have found PI3K/Akt to be a powerful survival pathway in numerous systems; cells can accelerate apoptosis by inhibiting PI3K and decelerate apoptosis by activating Akt (Hemmings and Restuccia, 2012). It was found that a decrease of caspase-9 activation could indicate the cardioprotective effects against diabetic cardiomyopathy by inhibiting cardiomyocyte apoptosis (Sun et al, 2014;Yu H.T. et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Oxidative stress is a notorious factor in the development of degenerative and age-related diseases such as diabetes (Lee et al, 2007;Hosaka et al, 2011;Yu et al, 2015), cancer (Lee et al, 2013;Zhu, 2016), immunity (Yu et al, 2016), liver injury (Zhang et al, 2014;Pang et al, 2015), cardiovascular (Andriantsitohaina et al, 2012) and neurodegenerative diseases (Choi et al, 2015). Oxidative stress-induced perturbations in the antioxidant defence systems of the body lead to DNA damage and cellular dysfunction, which is further linked to diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…The studies [81] of human atrium samples in vitro performed after reoxygenation and perfusion that modelled ischemia revealed the cell apoptosis and necrosis stronger expressed in patients with type I and type II diabetes mellitus. In rats with streptozotocininduced diabetes, the apoptosis of myocardial cells was also observed [74].…”
Section: J Of Biomedical Photonics and Eng 4(2)mentioning
confidence: 98%
“…The aging of organism is accompanied by structural and functional modifications of macromolecules [70]. The changes that occur in the tissues of the organism under the development of diabetes mellitus are investigated both in laboratory animals using experimental models [9][10][11]17, 39, 40, 42, 45-47, [71][72][73][74][75][76][77] and directly in patients in the course of clinical examination [12,35,[78][79][80][81][82][83][84][85][86][87].…”
Section: Classification Of Diabetes Mellitusmentioning
confidence: 99%